Readiness to quit smoking among smokers in substance use treatment: associations with stress, substance use severity, relapse concerns and gender. (2nd November 2021) - Xie, Siwen; Minami, Haruka; Selva Kumar, Danusha; Hecht, Jacki; Litvin Bloom, Erika; Kahler, Christopher W.; Abrantes, Ana; Price, Lawrence H.; Ondersma, Steven; Brown, Richard A.
ABSTRACT: Smoking prevalence among individuals in substance use treatment remains higher than in the general population. Given that many smokers in substance use treatment are reluctant to quit smoking, it is important to understand the factors that impede smokers' readiness to quit. The current study used baseline data from a randomized controlled trial involving 60 adult smokers receiving substance use treatment to investigate relations between the severity of substance use problems (SSUP), perceived stress (PS), concerns about relapse (i.e., concerns that quitting smoking would hurt one's recovery process (CR)), and readiness to quit smoking. This study also investigated moderating roles of concerns about relapse and gender. Regression analyses showed a significant main effect of concerns about relapse on readiness to quit in the next 30 days, but no effect for either severity of substance use problems, perceived stress, or the SSUPxCR interaction. There were significant interaction effects between PS and both gender and CR. Among men and those with lower concerns about relapse, higher perceived stress was significantly associated with lower readiness to quit. Findings suggest that psychoeducation to alleviate concerns that quitting smoking could limit substance use recovery could be beneficial. Stress management interventions may be especially beneficial to men.